Zastosowanie multimediów w edukacji humanistycznej = Application of multimedia in humanistic education - Kobyłecka, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
Taking advantages of educational software, LCD projector or Internet is necessary, also in case humanistic subjects teachers. Modern information's technology should be used in classroom everyday, makes teaching and learning of native language easier.
Keywords: multimedia; edukacja humanistyczna